Contributions of infrared thermography in the ergonomic evaluation of products: : case studies (Human Factors in Design, 2022)
This article aims to identify the contributions of infrared thermography (IRT) in the ergonomic evaluation of products, presenting two case studies. The results confirm that IRT is a safe, non-invasive and efficient method for: (1) evaluating products and users; (2) verify product-user relationships; (3) identifying discomforts; (4) understand the behavior of structures and materials; (5) diagnose design problems and; (6) evaluate alternatives. However, it can be considered as a viable resource for carrying out ergonomic evaluations, contributing to the development of safer, more comfortable and suitable products for users.